Equilibrium and kinetic study on the adsorption of basic dye (BY28) onto raw Ca-bentonite - Kalpakli, Yasemen; Toygun, Safak; Konecoglu, Gulhan; Akgun, Mesut (DESALINATION PUBL, 2014)
The adsorption of Basic Yellow 28 (BY28) onto bentonite in a batch system was carried out at temperatures of 20 and 40 degrees C. The initial dye concentrations were in the range of 100 and 300 mg/L based on the total organic carbon (TOC) content of the dye solution. The effects of contact time, initial pH, and initial dye concentration on BY28 adsorption by the bentonite have been studied. BY28 removal was observed to increase until equilibrium, with increasing contact time and initial dye concentration, and the adsorption capacity of bentonite was seen to increase with increasing pH from 3 to 8. Adsorption efficiencies up to about 98.1% were obtained based on the TOC at various adsorption conditions. The adsorption process was determined to follow the pseudo-second-order adsorption kinetics. Kinetic parameters, rate constants, equilibrium adsorption capacities, and correlation coefficients of the adsorption kinetic models were calculated and discussed. The experimental isotherm data were analyzed using the Langmuir and Freundlich equations. The Langmuir isotherm represents that the adsorption of BY28 is indicating a very good mathematical fit compared with the Freundlich equation. The maximum monolayer adsorption capacity (q(max)) of the Ca-bentonite was determined as 94.3396 mg/g for 20 degrees C and 99.0295 mg/g for 40 degrees C.
Keywords: Dye; Adsorption; Basic Yellow 28; Adsorption kinetics; Bentonite; AQUEOUS-SOLUTIONS; WASTE-WATER; AZO-DYE; HYDROXY-ALUMINOSILICATE; REACTIVE DYES; TEXTILE DYE; REMOVAL; OXIDATION; DECOLORIZATION; HYDROXYALUMINUM; Engineering; Water Resources